Semantični tekstovi makrounïversalïï v ukrainsʹkih narodnih dumah - Becenko, Tetâna (Stylistyka, 2008)
Clause is devoted to consideration of semantics, structure and poetic functions semantic text universalies as characteristic for ballades the epos textforming units. During research it is revealed, that analyzed structures on semantics can be incorporated thematically. Such structures most are frequently certified with семами conversation, trouble, damnation, site, never; etc. As a whole semantic text Maxpouniversalies represent predicative text universalies, in the majority such, that are expressed by a compound sentence: the complex syntactic whole or a complex syntactic design; such formations are characterized by the maximal cohesion of components therefore they get aphoristic sense.